Application of the Conceptual Model of Holistic Midwifery Services to Pregnant Women in Independent Practicing Midwives in Purwakarta Regency - ‘Aini, Qurotul (Archives of The Medicine and Case Reports, 2024)
Holistic midwifery services are an approach that views pregnant women as complete beings, consisting of physical, mental, social and spiritual aspects. The aim of this research is to determine the application of the conceptual model of holistic midwifery services to pregnant women in independent practice midwives in Purwakarta Regency. This research uses a qualitative approach with a case study method. The research subjects were 5 independent practicing midwives in Purwakarta Regency. Data was collected through in-depth interviews and observations. Data analysis was carried out descriptively qualitatively. The research results show that the implementation of the conceptual model of holistic midwifery services for pregnant women in independent practice midwives in Purwakarta Regency is quite good. Midwives are able to carry out holistic assessments of pregnant women, covering physical, mental, social and spiritual aspects. Midwives are also able to provide holistic midwifery care, including physical, mental, social and spiritual care.